Pore characteristics and preservation mechanism of over-6000-m ultra-deep shale reservoir in the Sichuan Basin - Xie, Guoliang; Jiao, Kun; Deng, Bin; Hao, Weiduo; Liu, Shugen (Frontiers in Earth Science, 2023)
Investigation of pore characteristics and their preservation mechanism of over 6000 m ultra-deep shale reservoirs is of significance for shale gas exploration and development in the Sichuan Basin. In this study, the pores structure and multifractal characteristics of pores for the Longmaxi shale and Qiongzhusi shale in the Sichuan Basin are well studied by using field emission scanning electron microscopy (FE-SEM), gas adsorption and multifractal analysis. The results show that: (1) Extremely strong mechanical compaction resulting from ultra-deep burial depth can lead to the homogenization of pore structure, which is characterized by the change of bubble-like OM pores to silt or fracture shape pores and the higher average pore diameter (APD) value. (2) The Longmaxi shale and Qiongzhusi shale reservoirs have the obvious multifractal nature for different pore sizes. Samples from the Longmaxi shale and Qiongzhusi shale in well CS#1 demonstrate the higher average H values and smaller average ΔD values compared with those samples in well MS#1, indicating that shale reservoir in over-pressure condition has higher connectivity and less heterogeneity. The pore preservation in over 6000 m ultra-deep shale reservoirs are influenced by several geological factors, including 1) quartz is beneficial for the preservation of pores especially for OM pores due to its supporting effect; 2) the shale reservoirs in over-pressure show many more OM pores and higher surface porosity than those in normal pressure; 3) the direct floor of Qiongzhusi shale is likely the critical geological factor affecting the pores preservation. Therefore, the Longmaxi shale with both over-pressure condition and high quartz content is likely the best target zone for deep shale gas exploration in the Sichuan Basin.